PWM 컨버터를 이용한 계통연계형 태양광발전 시스템 - 金大均(Dae-Gyun Kim); 全基英(Kee-Young Jeon); 咸年根(Nyon-Kun Hahm); 李丞桓(Seung-Hwan Lee); 吳鳳煥(Bong-Hwan Oh); 李勳九(Hoon-Goo Lee); 韓慶熙(Kyung-Hee Han); Choon-Byeong Chung(정춘병) (전기학회 논문지 P권, 54(3), 2005)
Since the residential load is an AC load and the output of solar cell is DC power, the photovoltaic system needs the DC/AC converter to utilize solar cell. In case of driving to interact with utility line, in order to operate at unity power factor, converter must provide the sinusoidal wave current and voltage with same phase of utility line. Since output of solar cell is greatly fluctuated by insolation, it is necessary that the operation of solar cell output in the range of the vicinity of maximum power point. In this paper, DC/AC converter is three phase PWM converter with smoothing reactor. And then, feed-forward control used to obtain a superior characteristic for current control and digital PLL circuit used to detect the phase of utility line.